(-4n-3n)x-8=

Simple and best practice solution for (-4n-3n)x-8= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-4n-3n)x-8= equation:


Simplifying
(-4n + -3n) * x + -8 = 0

Combine like terms: -4n + -3n = -7n
(-7n) * x + -8 = 0

Remove parenthesis around (-7n)
-7n * x + -8 = 0

Multiply n * x
-7nx + -8 = 0

Reorder the terms:
-8 + -7nx = 0

Solving
-8 + -7nx = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -7nx = 0 + 8

Combine like terms: -8 + 8 = 0
0 + -7nx = 0 + 8
-7nx = 0 + 8

Combine like terms: 0 + 8 = 8
-7nx = 8

Divide each side by '-7x'.
n = -1.142857143x-1

Simplifying
n = -1.142857143x-1

See similar equations:

| 3(r+2)=-1(24-12) | | (9x^2/10)*(7/10x) | | 2+5=65-2x | | 6(2-2w)=-12 | | 5(3-3b)=15 | | 4(2t+9)=-28 | | 6(1a+4)=30 | | 56+12(x)=80+8(x) | | (16x^2-5)-(4x^2+10)= | | 4(1n+5)=20 | | 11=6/7^3x | | 4(7m-2)=-8 | | 5x+18=6x+12 | | 4(-3x-3)=-120 | | .75m+32=47 | | 7(3w-4)=-238 | | 2(8-w)=32 | | 3(-5w+3)=129 | | 7(-7t-7)=539 | | 3(6+5t)=-117 | | 6-8x-3=-66+6x-15 | | 5x+22=3+8x-5 | | 1/5(7y-2)+1/10(6y+7) | | 7(-2n+5)=77 | | 70+27x+2=180 | | 2(1x+6)=34 | | 8n^2-13n+5= | | 2(-10+3m)=-14 | | -12=x-3 | | -6m-2m=-8 | | 3(6n+9)=63 | | 4(3d+3)=24 |

Equations solver categories